A historicidade da geometria e da astronomia a partir da cheia do rio Nilo - DAMASCENO, Luana Campos (2022)
The article has as its theme some records that deal with the Historicity of Geometry and its relations with Astronomy from the measurement of land, in the period of the flood of the Nile River. Its general objective is to analyze the history of geometry and astronomy: from the flood of the Nile River. And the specifics: identify the historicity of the geometry and astronomy of the flood of the Nile River; describe how the historical process of geometry and astronomy took place after the flooding of the Nile River; analyze historical process of astronomy geometry and its importance to humanity. The article was characterized by an exploratory study, of bibliographic modality. With a qualitative approach, Emfoque Crítica – Dialectic, this research has a qualitative nature. It was possible to understand that from the floods of the Nile River, the emergence of a geometry characterized by the design of shapes, formulas, calculation of area length measurements began. This work also highlighted the importance of the Nile River flood period for the development of land measurement (Geo) techniques, in addition to that, time measurements were also very important, since it is believed that the The first calendars appeared in Egypt, and their creation was due to the lack of accurate forecasting parameters in the planting seasons due to the flooding of the Nile River. As a result of this study, we hope to collaborate for the expansion of studies of Geometry and Astronomy, in mathematics classes, in Elementary School.